Recycling Nutrient Solution Can Reduce Growth Due to Nutrient Deficiencies in Hydroponic Production - Miller, Alexander; Adhikari, Ranjeeta; Nemali, Krishna (Frontiers in Plant Science, 2020)
It is common in hydroponics to supply nutrients to crops by maintaining electrical conductivity (EC) of the recycling solution at a target level. Levels of individual nutrients in the solution are generally not assessed as their regular measurement and adjustment can be both expensive and technically challenging. However, the approach of growing crops at a target EC can potentially result in nutrient imbalances in the solution and reduced growth. We quantified the effects of recycling on solution EC changes, tissue nutrient concentration, canopy growth rate, plant water status, and shoot and root weight of lettuce (Lactuca sativa) in a greenhouse. The tap water quality was moderately alkaline and similar to that commonly observed in many commercial greenhouses. In our research, recycling solution maintained at a target EC (1.8 dS·m-1) significantly reduced shoot fresh (22-36%) and dry weight compared to the control supplied regularly with freshly prepared solution at the target EC. Further, recycling significantly decreased N, P, K, and Fe and increased Na and Cu levels in the tissue, in addition to increasing solution EC between adjustments compared to the control. Using image analysis of groups of plants, we identified that the negative effects of recycling on canopy area started two weeks after transplanting. Based on these results, we hypothesized that certain unwanted compounds (e.g. bicarbonates) and slowly consumed elements (e.g. Ca, Mg) were added to the recycling solution through the alkaline tap water with time. Their accumulation ‘artificially’ increased solution EC and ‘masked’ the lower than optimal levels of major nutrients in the solution, leading to the reductions in the concentration of nutrients in the tissue and plant growth. Supporting this, the negative effects of recycling were not observed when the recycling solution was either discarded after two weeks of use or made using reverse osmosis water and continuously used. Our findings aid in proper management of recycling solution in hydroponic lettuce production.